Case Report: Metagenomic next-generation sequencing assists in dynamic pathogen monitoring: powerful tool for progressing severe pneumonia - Li, Yaoguang; Lei, Jun; Ren, Zhigang; Ma, Xiaoxu (Frontiers in Cellular and Infection Microbiology, 2023)
Background Severe community-acquired pneumonia (sCAP) is life-threatening and characterized by intensive care unit (ICU) admission and high mortality. And they are vulnerable to hospital-acquired infection. In such a severe condition, metagenomic next-generation sequencing (mNGS) outperforms for short turnaround time and broad detection spectrum. Case presentation A 15-year-old male with severe influenza and methicillin-resistant Staphylococcus aureus (MRSA) pneumonia progressed rapidly, initially misdiagnosed as influenza co-infected with Aspergillus for misleading bronchoscopy manifestations. The turnaround time of mNGS is 13 h, which has the potential to expedite the clinical medication process. With the powerful support of mNGS and extracorporeal membrane oxygenation (ECMO), anti-infective therapy was adjusted accordingly, and vital signs gradually stabilized. After tortuous treatment and unremitting efforts, the patient recovered well. Conclusions Rapid mNGS applications, timely medication adjustments, strong ECMO support and active family compliance contribute to this miracle of life. False-negative or false-positive results are alarming, anti-infective medications should be adjusted after a comprehensive review of physical status and other indicators.